A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Hays, Graeme C.; Koldewey, Heather J.; Andrzejaczek, Samantha; Attrill, Martin J.; Barley, Shanta; Bayley, Daniel T. I.; Benkwitt, Cassandra E.; Block, Barbara; Schallert, Robert J.; Carlisle, Aaron B.; Carr, Pete; Chapple, Taylor K.; et al. (Marine biology, 2020)
Given the recent trend towards establishing very large marine protected areas (MPAs) and the high potential of these to contribute to global conservation targets, we review outcomes of the last decade of marine conservation research in the British Indian Ocean Territory (BIOT), one of the largest MPAs in the world. The BIOT MPA consists of the atolls of the Chagos Archipelago, interspersed with and surrounded by deep oceanic waters. Islands around the atoll rims serve as nesting grounds for sea birds. Extensive and diverse shallow and mesophotic reef habitats provide essential habitat and feeding grounds for all marine life, and the absence of local human impacts may improve recovery after coral bleaching events. Census data have shown recent increases in the abundance of sea turtles, high numbers of nesting seabirds and high fish abundance, at least some of which is linked to the lack of recent harvesting. For example, across the archipelago the annual number of green turtle clutches ( Chelonia mydas ) is ~ 20,500 and increasing and the number of seabirds is ~ 1 million. Animal tracking studies have shown that some taxa breed and/or forage consistently within the MPA (e.g. some reef fishes, elasmobranchs and seabirds), suggesting the MPA has the potential to provide long-term protection. In contrast, post-nesting green turtles travel up to 4000 km to distant foraging sites, so the protected beaches in the Chagos Archipelago provide a nesting sanctuary for individuals that forage across an ocean basin and several geopolitical borders. Surveys using divers and underwater video systems show high habitat diversity and abundant marine life on all trophic levels. For example, coral cover can be as high as 40–50%. Ecological studies are shedding light on how remote ecosystems function, connect to each other and respond to climate-driven stressors compared to other locations that are more locally impacted. However, important threats to this MPA have been identified, particularly global heating events, and Illegal, Unreported and Unregulated (IUU) fishing activity, which considerably impact both reef and pelagic fishes.